Manajemen Penanaman Nilai-Nilai Toleransi Di Sekolah Menengah Kejuruan Negeri 1 Kuningan - Asep Kurniawan (Holistik, 2022)
Tolerance plays an important role in maintaining harmony in the life of a plural society. This study aimed to reveal in-depth the management of instilling the values of tolerance in State Vocational High School 1 Kuningan. This research used descriptive analytical-qualitative method. Data collection used in-depth observation, unstructured and in-depth interviews, and documentation. The research subjects were students, teachers, staffs, vice principals, school principals, and community leaders. Technical data analysis was done through data reduction, data display, and data inference. The results showed that the management of instilling tolerance values in State Vocational School 1 Kuningan was carried out in several stages (1) planning was done through a vision and mission then integrated into the curriculum. (2) Organizing was done by grouping the implementation of activities coordinated through school public relations. (3) Implementation of instilling tolerance values was inserted in the classroom learning, and then applied in an attitude of respecting differences with other religions and participation in certain religious ceremonies, as long as they did not conflict with students’ beliefs. (4) Controlling and evaluation focused on providing advice.